Hematological Responses, Survival, and Respiratory Exchange in the Olive Flounder, Paralichthys olivaceus, during Starvation - Park, I.-S. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
A 12-wk experiment was conducted to examine the hematological changes, survival, and respiratory exchange in the olive flounder, Paralichthys olivaceus, during starvation. The growth, survival and respiratory exchange rates of the starved group were lower than those of the fed group during the experiment. Blood analysis, including hematocrit, hemoglobin, red blood cells, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and mean corpuscular volume, did not differ significantly (p>0.05) between the fed and starved groups at the end of the experiment. There were no significant differences in plasma cortisol, glucose, Na(+), Cl(−), K(+), or aspartate aminotransferase between the fed and starved groups (p>0.05). Alanine aminotransferase levels were higher in the starved group than in the fed group, whereas plasma osmolality was lower in the starved group than in the fed group. It was shown that starved fish had various problems after four weeks, which did not occur in the fed group. Long-term starvation is infrequent in aquaculture farms. However, starvation studies of this kind are very useful for a basic understanding of how physiological changes affect fish health, life expectancy, and growth.